Heart Failure and Palliative Care: Implications in Practice - Hupcey, Judith E. (Mary Ann Liebert, Inc., 2009)
The number of people with heart failure is continually rising. Despite continued medical advances that may prolong life, there is no cure. While typical heart failure trajectories include the risk of sudden death, heart failure is typically characterized by periods of stability interrupted by acute exacerbations. The unpredictable nature of this disease and the inability to predict its terminal phase has resulted in few services beyond medical management being offered. Yet, this population has documented unmet needs that extend beyond routine medical care. Palliative care has been proposed as a strategy to meet these needs, however, these services are rarely offered. Although palliative care should be implemented early in the disease process, in practice it is tied to end-of-life care. The purpose of this study was to uncover whether the conceptualization of palliative care for heart failure as end-of-life care may inhibit the provision of these services. The meaning of palliative care in heart failure was explored from three perspectives: scientific literature, health care providers, and spousal caregivers of patients with heart failure. There is confusion in the literature and by the health care community about the meaning of the term palliative care and what the provision of these services entails. Palliative care was equated to end-of-life care, and as a result, health care providers may be reluctant to discuss palliative care with heart failure patients early in the disease trajectory. Most family caregivers have not heard of the term and all would be receptive to an offer of palliative care at some point during the disease trajectory.